Cardiorenal Nexus: A Review With Focus on Combined Chronic Heart and Kidney Failure, and Insights From Recent Clinical Trials - Peter A. McCullough; Alpesh Amin; Kevin M. Pantalone; Claudio Ronco (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2022)
The cardiorenal nexus encompasses a bidirectional relationship between the heart and the kidneys. Chronic abnormalities in cardiac function can lead to progressive kidney disease, and chronic kidney disease can lead to progressively decreasing cardiac function and increasing risk of cardiovascular disease, including heart failure. About 15% of US adults have chronic kidney disease, 2% have heart failure, and 9% have cardiovascular disease. Prevalence rates of chronic kidney disease, cardiovascular disease, and associated morbidities such as type 2 diabetes are expected to increase with an aging population. Observational studies provide evidence for the cardiorenal nexus. Follow‐up data from placebo arms of clinical trials in chronic kidney disease or cardiovascular disease show higher rates of renal and cardiovascular outcome events in patient subgroups with type 2 diabetes than in those without type 2 diabetes. The cardiorenal syndromes develop along an interlinked pathophysiological trajectory that requires a holistic, collaborative approach involving a multidisciplinary team. There is now a compendium of treatment options. Greater understanding of the underlying pathophysiology of the cardiorenal nexus will support optimization of the management of these interlinked disease states.